Prenatal molecular diagnosis in RASA1‐related disease. (21st November 2017) - Palmyre, Aurélien; Eyries, Mélanie; Senat, Marie‐Victoire; Ozanne, Augustin; Staraci, Stéphanie; Dufour, Philippe; Chinet, Thierry; Lacombe, Pascal; Soubrier, Florent; Charron, Philippe
Abstract: RASA1‐ related disease is a rare autosomal dominant disease characterized by capillary malformations, arteriovenous malformations (AVMs), and/or arteriovenous fistulas (AFVs). Penetrance is nearly complete and vascular malformations may cause serious complications such as organ injury due to oxygenation disorder, brain abscess, hemorrhage, and stroke. Early diagnosis is useful in order to discuss optimal management, including AVMs/AVFs embolization or surgical procedures, and try to prevent some of the complications. In this context, molecular testing of RASA1 gene mutation in relatives may help to better manage the family. All arteriovenous malformations are however not accessible to such procedures. In addition, these therapeutic procedures may result in potential side effects and complications. A couple was referred to our genetics unit and asked us for prenatal genetic testing about a RASA1 mutation. Here, we discuss about arguments that led our team to accept prenatal testing. To the best of our knowledge, no molecular prenatal diagnosis was reported until now in RASA1 ‐related diseases. This first report of prenatal diagnosis in RASA1 ‐related diseases may also offer perspectives for a more general discussion in the field of inherited arteriovenous malformations. Abstract : What's already known about this topic? RASA1‐ related diseases are autosomal dominant diseases characterized by capillary malformations, arteriovenous malformations, and/or arteriovenous fistulas. Predictive molecular diagnosis is proposed to relatives of RASA1 ‐mutated patient, to allow early diagnosis and appropriate medical management. No molecular prenatal diagnosis is reported until now in RASA1 ‐related diseases. What does this study add? This case report illustrates the complex impact and the feasibility of prenatal molecular diagnosis for RASA1 ‐related diseases. This appeared as a reasonable option after a collegial multidisciplinary discussion.